How does the perceived green human resource management impact employee’s green innovative behavior? —From the perspective of theory of planned behavior - Song, Dian; Bai, Yan; Wu, Hainan; Wang, Xiaoyuan (Frontiers in Psychology, 2023)
Employees’ green innovative behavior encouraged by enterprises plays an important role in sustainable development. Drawing upon the planned behavior theory, this study examines how perceived green human resource management impact employees’ green innovation behavior. Based on the survey of 207 employees, data analysis shows that perceived green human resource management has a positive effect on employees' green innovative behavior via green intention, self-efficacy of environmental protection behavior, and identity with the company’s green environmental protection system. Meanwhile, the results demonstrate that there is a chain mediating relationship among these variables. In addition, green supply chain management moderates the relationship between the identity of a green environmental protection system and green innovation behavior.